2023
DOI: 10.1021/acs.biochem.3c00260
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Binding of Four Adenosine/ATP Aptamers to Caffeine, Theophylline, and Other Methylxanthines

Abstract: The classical DNA aptamer for adenosine and ATP was selected twice using ATP as the target in 1995 and 2005, respectively. In 2022, this motif appeared four more times from selections using adenosine, ATP, theophylline, and caffeine as targets, suggesting that this aptamer can also bind methylxanthines. In this work, using thioflavin T fluorescence spectroscopy, this classical DNA aptamer showed K d values for adenosine, theophylline, and caffeine of 9.5, 101, and 131 μM, respectively, and similar K d values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Upon target binding, a fraction of the ThT is displaced and decreased fluorescence is observed. Thioflavin T has been used in many non‐G‐quadruplex aptamers [32,33] . We mixed 1 μM SA1 aptamer and 2 μM ThT and then gradually titrated SA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon target binding, a fraction of the ThT is displaced and decreased fluorescence is observed. Thioflavin T has been used in many non‐G‐quadruplex aptamers [32,33] . We mixed 1 μM SA1 aptamer and 2 μM ThT and then gradually titrated SA.…”
Section: Resultsmentioning
confidence: 99%
“…Thioflavin T has been used in many non-G-quadruplex aptamers. [32,33] We mixed 1 μM SA1 aptamer and 2 μM ThT and then gradually titrated SA. A gradual drop in the ThT fluorescence at 490 nm was observed, and eventually more than 50% fluorescence drop was achieved (Figure 2d, black trace).…”
Section: Tht-based Binding Assaysmentioning
confidence: 99%
“…In another study, we found that two of adenosine binding aptamers can also bind theophylline and caffeine. [15] Given the physiological relationship between theophylline, caffeine, and adenosine in the regulation of sleep and their binding to the same protein receptors, our discovery may imply that nucleic acid versions of receptors can also bind to both molecules. While it is unknown that this point whether primitive organisms might have used RNA to regulate their biological processes such as sleep, nucleic acids certainly have the chemical capacity to perform this task.…”
Section: Discussionmentioning
confidence: 95%
“…We then tried a label-free fluorescent assay using thioflavin T (ThT) (Figure 3A). [15,[30][31] Using 100 nM Theo2201 aptamer and 2 μM ThT dye, we monitored the fluorescence of ThT at 490 nm. As shown in Figure 3B, a drop in the ThT fluorescence was observed upon titration of 100 μM theophylline.…”
Section: The Theo2201 Aptamer Can Bind Adenosinementioning
confidence: 99%
See 1 more Smart Citation